2014
DOI: 10.1016/s0325-7541(14)70091-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and physicochemical analysis of yateí (Tetragonisca angustula) honey for assessing quality standards and commercialization

Abstract: Due to the interest in the production and trading of yateí (Tetragonisca angustula) honey in the province of Misiones, Argentina, in this work we assessed microbiological and physicochemical parameters in order to contribute to the elaboration of standards for quality control and promote commercialization. Results showed that yateí honey samples had significantly different microbiological and physicochemical characteristics in comparison to established quality standards for Apis mellifera honey. Thus, we obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
48
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 26 publications
5
48
0
3
Order By: Relevance
“…All samples tested were negative for Salmonella spp., in agreement with other studies evaluating the honey from SB (MONTE et al, 2013;PUCCIARELLI et al, 2014). Some studies have shown the antibacterial effect of honey, and the honey from SB in particular, against a wide range of bacteria, including Salmonella (PIMENTEL et al, 2013;NISHIO et al, 2016).…”
supporting
confidence: 92%
See 2 more Smart Citations
“…All samples tested were negative for Salmonella spp., in agreement with other studies evaluating the honey from SB (MONTE et al, 2013;PUCCIARELLI et al, 2014). Some studies have shown the antibacterial effect of honey, and the honey from SB in particular, against a wide range of bacteria, including Salmonella (PIMENTEL et al, 2013;NISHIO et al, 2016).…”
supporting
confidence: 92%
“…in the honey from SB is rare. Equipment and physical honey handling are considered the main sources of contamination by this microorganism (DÜMEN et al, 2013;PUCCIARELLI et al, 2014). In addition, the antimicrobial activities of honey against grampositive bacteria, specifically Staphylococcus spp., were also evaluated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Potato glucose agar in Brazil was also used for monitoring the honey contamination by yeast and fungi [144]. Standard plate count agar is used for monitoring of mesophilic bacteria, such as that was done in honey samples of Portugal [141,142] and Argentina [119,145].…”
Section: Monitoring Of the Microbiological Honey Qualitymentioning
confidence: 99%
“…Some Bacillus species associated with stingless bees were isolated from Melipona panamica (B. alvei and B. circulans) and Trigona necrophaga (B. circulans, B. licheniformis, B. megaterium, B. pumilus and B. subtilis) nests in Panama (Gilliam, 1997). Moreover, other bacterial genera including Streptomyces (Promnuan, Kudo & Chantawannakul, 2009), Clostridium, Staphylococcus, Enterobacter (Pucciarelli et al, 2014), Ralstonia, Pantoea, Neisseria, Pseudomonas (Leonhardt & Kaltenpoth, 2014), Lysinibacillus (Shanks et al, 2017) and Fructobacillus (Yaacob et al, 2018) also have be found associated with stingless bees.…”
Section: Introductionmentioning
confidence: 99%